Intersections Between the Intercultural Education Ethos and the Integral Ecological Ethics for the Common Home - Ana Maria Eyng; Aline Vicentim Villas Boas (Religions)
This study critically analyses the urgency of establishing an ethos of discourse and action for the realization of an integral planetary ethic that is capable of addressing the challenges of our time. To this end, this study seeks to systematize ethos propositions for the implementation of intercultural education based on integral ecological ethics, aligning with the concept of Common Home. The outputs indicate that integral ecological ethics serves as a teleological, epistemic, and methodological support for intercultural education, while also proposing concrete pathways for the application of the values articulated in the encyclical Laudato si’ within educational contexts. The development of this study is guided by a qualitative research approach, integrating literature review and field study methodologies, which illuminate the perspectives of educators, students, and their families regarding well-being in both current and future contexts. The conclusions underscore the urgency of establishing an ethos of discourse and action in the implementation of integral planetary ethics, which relates to the integrative and dialogical propositions of intercultural education aimed at sustaining the integrity of both human and planetary dimensions.